Dissection of the HOG pathway activated by hydrogen peroxide in Saccharomyces cerevisiae. (7th September 2016) - Lee, Young Mi; Kim, Eunjung; An, Jieun; Lee, Yeji; Choi, Eunyong; Choi, Wonja; Moon, Eunpyo; Kim, Wankee
Summary: Cells usually cope with oxidative stress by activating signal transduction pathways. In the budding yeast Sacchromyces cerevisiae, the high osmolarity glycerol (HOG) pathway has long been implicated in transducing the oxidative stress‐induced signal, but the underlying mechanisms are not well defined. Based on phosphorylation of the mitogen‐activated protein kinase (MAPK) Hog1, we reveal that the signal from hydrogen peroxide (H2 O2 ) flows through Ssk1, the response regulator of the two‐component system of the HOG pathway. Downstream signal transduction into the HOG MAPK cascade requires the MAP kinase kinase kinase (MAP3K) Ssk2 but not its paralog Ssk22 or another MAP3K Ste11 of the pathway, culminating in Hog1 phosphorylation via the MAP2K Pbs2. When overexpressed, Ssk2 is also activated in an Ssk1‐independent manner. Unlike in mammals, H2 O2 does not cause endoplasmic reticulum stress, which can activate Hog1 through the conventional unfolded protein response. Hog1 activated by H2 O2 is retained in the cytoplasm, but is still able to activate the cAMP‐ or stress‐responsive elements by unknown mechanisms.